REDUPLICATION IN THE LOCAL LANGUAGE PAK-PAK BOANG SUBULUSSALAM CITY, ACEH PROVINCE, INDONESIA - Yulsafli, Yulsafli (SCAD Independent, 2016)
This paper examined the reduplication of Pak?Pak Boang language which consists of many reduplication, the speakers of the language are situated in the Rundeng, Subulussalam, Aceh Province. The research aspects to explore are types of reduplication and the forms produced through the reduplication of the language. The purpose of this paper is to describe the types and forms of Pak-Pak Boang language. The method applied in this research was qualitative descriptive, where the data gained through recording, documentary study, and introspection. The result of the findings showed that Pak-Pak Boang language reduplication consisted of four types: Phonology, syntaxes, semantics, and morphology reduplication. The second finding revealed that the reduplication forms were Dwilingga, Dwipurwa, Dwiwasana, and trilingga reduplication, while the process to form reduplication consisted of seven ways: Adjective, Verb, noun, Pronoun, Adverb, Interrogative, and Number reduplication.